Real-world misuse, abuse, and dependence of abuse-deterrent versus non-abuse-deterrent extended-release morphine in Medicaid non-cancer patients. Issue 3 (3rd April 2019) - Cicero, Theodore J.; Mendoza, Mario; Cattaneo, Michael; Dart, Richard C.; Mardekian, Jack; Polson, Michael; Roland, Carl L.; Schnoll, Sidney H.; Webster, Lynn R.; Park, Peter W.
ABSTRACT: Objective : Opioids with abuse-deterrent properties may reduce widespread abuse, misuse, and diversion of these products. This study aimed to quantify misuse, abuse, dependence, and health resource use of extended-release morphine sulfate with sequestered naltrexone hydrochloride (ER-MSN; EMBEDA®), compared with non-abuse-deterrent extended-release morphine (ERM) products in Medicaid non-cancer patients. Methods : Administrative medical and pharmacy claims data were analyzed for 10 Medicaid states from 1 January 2015, to 30 June 2016. Patients were included if they received a prescription for ER-MSN or any oral, non-abuse-deterrent ERM. Index date was the date of first prescription for an ER-MSN or ERM. Abuse/dependence, non-fatal overdose, emergency department (ED) visits, and ED/inpatient readmissions were determined for each participant. An overall measure of misuse and abuse was also calculated. To account for differences in follow-up, all counts are expressed per 100 patient-years. Results : There were 4, 857 patients who received ER-MSN and 10, 357 who received an ERM. The average age in the two cohorts was approximately 45 years old. From pre-index to follow-up, the number of patients per 100 patient-years with a diagnosis code indicating abuse or dependence increased by 0.91 (95% confidence interval [CI]: 0.85, 0.97) in the ER-MSN cohort and 2.23 (95% CI: 2.14, 2.32) in the ERM cohort. The number of patients per 100 patient-years with an opioid-related non-fatal overdose increased by 0.05 (95% CI: 0.04, 0.06) in the ER-MSN cohort compared with 0.11 (95% CI: 0.09, 0.13) in the ERM cohort. The opioid abuse overall composite score increased by 1.36 (95% CI: 1.24, 1.48) in the post-index period in the ER-MSN cohort compared to 3.21 (95% CI: 3.10, 3.32) in the ERM cohort. Conclusion : Misuse, abuse, and dependence events were numerically lower in patients receiving ER-MSN compared with those receiving ERM products.